The Mangrove Ecosystem Health Condition Evaluation in Citeureup Village, Pandeglang Regency, Banten Province - Ghaishidra, Paspha; Ghifar Naufa, Aslam; Ganang Rahmandika, Priandono; Zainuri Sofyan, Bisri; Rudhi, Pribadi; Eren Putra , Febrio (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2024)
Mangrove in Citeureup Village, Panimbang District, Pandeglang Regency is a mangrove area that is located at the western coastal of Java Island. Panimbang District is one of areas in Pandeglang District where abrasion occurs. Almost half of the shoreline having damaged that is caused by abrasion. In 2010, the damaged mangrove area in Panimbang District was 37.07 ha wide. Meanwhile, for the mangrove area in Citeureup Village, still no data available that specifically defines the condition of that area. Hence, the study about analytical approach of mangrove vegetation for knowing the mangrove health in that area is needed to be done. The sample retrieval was located in Citeureup Village, Panimbang District, Pandeglang Regency. The method of mangrove health evaluation integrating vegetation analysis and canopy cover quantification, the location determination was determined by purposive sampling. The result of this study showed that the mangrove ecosystem condition in Citeureup Village, Pandeglang Regency, Banten Province was in a good condition since it has the average value of >1,500 ind/ha in every station. The mangrove composition was dominated by the species of A. marina and A. alba. A. marina species was dominating all of the research area. The structure of mangrove vegetation had the mangrove density with tree category was around 2,350-5,167 ind/ha, this condition showed that it was in a good category. The percentage of canopy cover was categorized as moderate to dense with 51.95-93.18%. The percentage value of canopy cover is affected by the mangrove density and the dominating species.